Hematopoietic stem cells contribute to lymphatic endothelium. - Shuguang Jiang; Alexis S Bailey; Devorah C Goldman; John R Swain; Melissa H Wong; Philip R Streeter; William H Fleming (PLoS ONE)
Background Although the lymphatic system arises as an extension of venous vessels in the embryo, little is known about the role of circulating progenitors in the maintenance or development of lymphatic endothelium. Here, we investigated whether hematopoietic stem cells (HSCs) have the potential to give rise to lymphatic endothelial cells (LEC). Methodology/principal findings Following the transfer of marked HSCs into irradiated recipients, donor-derived LEC that co-express the lymphatic endothelial markers Lyve-1 and VEGFR-3 were identified in several tissues. HSC-derived LEC persisted for more than 12 months and contributed to approximately 3-4% of lymphatic vessels. Donor-derived LECs were not detected in mice transplanted with common myeloid progenitors and granulocyte/macrophage progenitors, suggesting that myeloid lineage commitment is not a requisite step in HSC contribution to lymphatic endothelium. Analysis of parabiotic mice revealed direct evidence for the existence of functional, circulating lymphatic progenitors in the absence of acute injury. Furthermore, the transplantation of HSCs into Apc(Min/+) mice resulted in the incorporation of donor-derived LEC into the lymphatic vessels of spontaneously arising intestinal tumors. Conclusions/significance Our results indicate that HSCs can contribute to normal and tumor associated lymphatic endothelium. These findings suggest that the modification of HSCs may be a novel approach for targeting tumor metastasis and attenuating diseases of the lymphatic system.